Detecting apathy in patients with cerebral small vessel disease - Cai, Xiaoping; Zhào, Hóngyi; Li, Zhiyi; Ding, Yu; Huang, Yonghua (Frontiers in Aging Neuroscience, 2022)
Background: Apathy is attracting more and more attention in clinical practice. As one the most common features of Cerebral Small Vessel Disease (CSVD), the assessment of apathy still mainly relies on observers. With the development of Information and Communication Technologies (ICTs), new objective tools take part in the early detection of apathy. Objectives: To detect apathy in patients with CSVD, and find out the relationship between apathy and actigraphic data sampled from diurnal and nocturnal period. Methods: A total of 56 CSVD patients were recruited for a cross-sectional observational study. Apathy was diagnosed by the diagnostic criteria for apathy in neurocognitive disorders. The Magnetic Resonance Imaging (MRI) presence of lacunes, white matter hyperintensities, cerebral microbleeds, and perivascular spaces were rated independently. Actigraph devices were worn in nondominant hand of each subject for 7 consecutive days to sample raw data, and diurnal Vector Magnitude (VM) as well as a series of sleep quality variables were obtained. Results: We found that the frequency of apathy in Chinese CSVD patients reached 37.50%. Apathy+ group patients showed more lacunes and Cerebral Microbleeds (CMBs), higher Fazekas score in comparison to apathy- group individuals. Diurnal VM, instead of other sleep quality variables, were lower in CSVD patients with apathy relative to those without apathy. Lastly, we discovered that diurnal VM and Total Time in Bed (TTB) correlated negatively with apathy severity in CSVD patients. Conclusion: Actigraphy is a promising choice to evaluate apathy in CSVD patients.